Ancient ivory masterpieces of the Assyrian empire - Herrmann, Georgina 1937- (Thames & Hudson, 2017)
Ivory is a wonderful material: tactile, beautiful, workable into many different forms and the strongest in the animal kingdom. Unfortunately for the elephant, it has been highly prized from the Palaeolithic to the present day, in part by virtue of its rarity and the difficulty of acquiring it. During the early first millennium bc - the "Age of Ivory" - literally thousands of carved ivories found their way to the Assyrian capital city of Kalhu, or modern Nimrud, in northern Iraq. The majority were not made there, in the heart of ancient Assyria, but arrived as gift, tribute or booty gathered by the Assyrian kings from the small neighbouring states of the ancient Middle Eastern world. The ivories were first unearthed in the mid-19th century by renowned Victorian traveller and adventurer Austen Henry Layard, but it was not until the mid-20th century that the extent of the treasure was realized by Max Mallowan, the archaeologist husband of Agatha Christie. Thousands of extraordinary ivories have since been excavated from the ruins of the ancient city's extravagant palaces, temples and forts